Exploration of the experiences, opinions and attitudes of nurses on inter-shift handover procedures - Rikos, Nikos; Linardakis, Manolis; Merkouris, Anastasios; Rovithis, Michael; Philalithis, Anastas (My University, 2019)
OBJECTIVE To explore the experiences, opinions, and attitudes of nurses regarding the nursing inter-shift handover process. METHOD A qualitative/ observational study was carried out at the University General Hospital of Crete, Greece from November 2015 to February 2016. Convenience sampling was used to choose 22 nurses (3 males/19 females, mean age 39.3±8.2 years) who worked shifts in the nursing departments, based on the hospital shift schedule. Data were collected using a semi-structured questionnaire with six open-ended questions, administered by recorded interview. Content and cluster analysis were performed of the responses. RESULTS The responses revealed a variety of experiences, requirements, deficiencies and convictions regarding the process that is, or should be, implemented for nursing handover at shift change. The main characteristics were related to the clinical condition and management of patients, lack of a common, systematic nursing handover method, lack of confidence of the nurses in their scientific knowledge and skills, need for systematization of, and critical approach to, information, and significant parameters for provision of optimum health care, need to design care plans based on best practice and need for training. CONCLUSIONS According to the experiences and opinions of the nursing staff, effective nursing handover can only be achieved with clearly defined clinical processes, using nursing diagnoses, and through the implementation of best nursing practice. A necessary precondition for achieving effective nursing handover is training on the methods of clinical information transfer, and its importance for ensuring patient safety.
Διερεύνηση των απόψεων, των πεποιθήσεων και των εμπειριών του νοσηλευτικού προσωπικού για τη διαδικασία των νοσηλευτικών ενημερώσεων
Keywords: Continuity of patient care; Health information; Nursing handover; Patient hand off; Quality care assurance